2020
DOI: 10.1017/s002185962000026x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of adding functional oils or sodium monensin in high-concentrate diets on performance, feeding behaviour and rumen morphometrics of finishing Nellore cattle

Abstract: This study, conducted at the São Paulo State University feedlot, Dracena campus, Brazil, was designed as a completely randomized block with 2 × 2 factorial arrangement of treatments to evaluate the effects of adding functional oils (FO) or sodium monensin (MON) on feedlot performance, carcass traits, feeding behaviour and rumen morphometrics of Nellore cattle. Ninety-six 20-mo-old Nellore bulls (365.52 ± 39.19 kg) were randomly allocated to 24 pens (n = 4/pen), which were assigned to the treatments: (1) Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
0
0
Order By: Relevance
“…In fact, the cattle fed VM14 had an increased DMI, as percent of BW, by 4.7% when compared to the cattle consuming MON14 ( Table 5 ), which may have contributed to greater fat deposition due to the increased amount of energy consumed throughout the study since no differences were observed for starch digestibility during adaptation or finishing ( Table 7 ). This negative effect of MON on carcass fat deposition, as shown in this study, has been reported previously by other authors ( 33 ), and it is potentially related to the decreasing molar proportion of ruminal acetate ( 34 ). Therefore, the impaired feed efficiency presented by the cattle fed VM14 may be partially attributed to more extensive fat deposition, which requires more energy or calories per gram of tissue than muscle accretion ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the cattle fed VM14 had an increased DMI, as percent of BW, by 4.7% when compared to the cattle consuming MON14 ( Table 5 ), which may have contributed to greater fat deposition due to the increased amount of energy consumed throughout the study since no differences were observed for starch digestibility during adaptation or finishing ( Table 7 ). This negative effect of MON on carcass fat deposition, as shown in this study, has been reported previously by other authors ( 33 ), and it is potentially related to the decreasing molar proportion of ruminal acetate ( 34 ). Therefore, the impaired feed efficiency presented by the cattle fed VM14 may be partially attributed to more extensive fat deposition, which requires more energy or calories per gram of tissue than muscle accretion ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Rigueiro et al (2020), evaluating feedlot performance of Nellore bulls receiving different combinations of virginiamycin (25 mg/kg of DM) and monensin (30 mg/kg of DM) during the adaptation and finishing periods, observed an improvement in overall productive performance when bulls were fed the additive combination only during the adaptation period; with no benefits when the combination was supplemented during the finishing period or the entire feeding period (adaptation and finishing). The authors postulated that their results reflected the absence of the negative impact of monensin on DMI, since bulls were supplemented with ionophore for the shortest period.…”
Section: Non-ionophores Antibioticsmentioning
confidence: 92%
“…Proper management of this phase may influence intake and performance throughout the feedlot period. According to Estevam et al (2020), one of the determining factors for the adaptation protocol is the energy content of finishing diets. According to these authors, systems that use less energy in the diets can reduce the adaptation periods without health problems and performance reduction.…”
Section: Adaptation For Feedlot Cattlementioning
confidence: 99%
See 2 more Smart Citations

Nutrient Requirements of Zebu and Crossbred Cattle - BR-CORTE

Sebastião de Campos,
Douglas Teixeira,
Pedro Del Bianco
et al. 2023